Kuliah Kerja Nyata Terpadu CSR Perusahaan Konstruksi Bagi Masyarakat - deden, deden (Universitas Negeri Makassar, 2023)
Real Work Lectures (KKN) is a form of community service carried out by students in an interdisciplinary, institutional and partnership manner as a form of higher education tridharma activities. As the social dynamics of society, regional government, central government and the global world change, the KKN program at Gunung Jati Swadaya University (UGJ) is directed at a KKN pattern based on community empowerment. CSR (Corporate Social Responsibility) has been popularly used in Indonesia since the 1990s. Several companies have actually been carrying out CSA (Corporate Social Activity) or